Pengaruh Locus of Control Dan Motivasi Belajar Terhadap Hasil Belajar - Priska Arinanda Yuni Fasari; Supri Wahyudi Utomo; Farida Styaningrum (JAMER : Jurnal Akuntansi Merdeka, 2021)
The purpose of this study was to determine the effect of Locus of Control and learning motivation on learning outcomes. The research design used a quantitative approach. The study used a population of class X accounting students of SMKN 2 Jiwan with a total of 161 students. The sample used was 115 students. The data collection technique was done by simple random sampling. The data sources used were primary data and secondary data. Data collection was carried out by means of a questionnaire in order to obtain data on the locus of control and learning motivation, meanwhile the learning outcomes were obtained from the average value of daily tests. Test instrument examiners used validity and reliability testing with Cronbach Alpha. The results of this study show 1) there is a significant positive effect of locus of control on learning motivation, 2) there is a significant positive effect of learning motivation on learning outcomes, 3) there is a simultaneous significant effect on learning outcomes.Â